Political patronage in election: Impacts of the Coalition Change in Malaysian Federal Government on Sarawak's Politics / Ivy Jugah and Arnold Puyok - Ivy, Jugah; Puyok, Arnold (2021)
In 2018, after the Malaysian 14th general election, the political realignment prompted the federal government to change its alliance from Barisan Nasional (BN) to another coalition named Pakatan Harapan (PH). However, PH's government only managed to serve for less than two years as the federal government when another political realignment happened again in early 2020, leading to the government's fall to the new Perikatan Nasional (PN) coalition. Malaysia, which practised federalism, faces a challenge because of the federal government's ongoing political turmoil. Sarawak has openly challenged the federal government over the last decade because of its decisiveness in national politics. After Malaysia's 14th general election in 2018, Sarawak became an opposition state for the first time, forming a new Barisan Nasional (BN) coalition called Gabungan Parti Sarawak (GPS). Despite various controversial issues such as the 1Malaysia Development Berhad scandal (1MDB), Malaysian Agreement 1963 (MA63), and oil and gas royalties used by opposition parties during campaigning periods, the Barisan Nasional political party remains strong, especially in Sarawak's rural areas. However, a sudden political realignment in the federal government will be very interesting to Malaysian politics, particularly in Sarawak, where the state election is scheduled for 2022.